Ethical values of public accountant: a critical perspective of rational-religious of Hamka - Muhammad, Erfan; Sudarma, Made; Djamhuri, Ali; Adib, Noval; Eliwa, Yasser (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This study explores business practices in public accounting firms, particularly in East Java, along with ethical issues raised by the practices.Method - This study applied a qualitative approach in which data were collected through in-depth interviews with 12 public accountants from various public accounting firms. Then, the data were analysed based on a rational-religious perspective as suggested by Buya Hamka.Result - The findings of this study indicated many ethical concerns in public accountant practices, despite they comprehend about ethical standards contained in the professional code of ethics. All those problems were actuated by the financial fulfillment of the public accountant, which deviated from ethical values as signified by Hamka.Implication - Public accountants should implement Hamka’s virtues in professional practices as a reflection of Islamic principles.Originality - This research is the first study that used the virtues of Buya Hamka in public accountant practices.